Effects of emerging chemical contaminants on water resources and environmental health - Shikuku, Victor, 1986- (Advances in environmental engineering and green technologies (AEEGT) book series., 2020)
""This book explores current issues dealing with the occurrence, toxicology, and abatement of emerging contaminants. It also examines new technologies and developments in sample preparation and detection of contaminants in water resources."--